Religious Pluralism: A Study of Nurcholish Madjid’s Thoughts - Imam Muhajir Putra; Mila Aulia; Alfian Ghofur; Ahmad Wahyu Sudrajad (Transformatif, 2023)
This study explains Nurcholish Madjid’s thoughts on religious pluralism in a descriptive-qualitative way. The reality of diversity in Indonesia today shows that the issue of pluralism is attributed to an understanding that is contrary to Islamic teachings. Such a perspective gives birth to an exclusicve Islam wich tends to ignore the contextualization of Islamic teachings (al-Qur’an) and sociological aspects. Whereas the Qur’an expressly hints at the similarity of Islam with the religion of the previous prophets, for example, the surah Ali Imran/3: 64 which contains ‘Kalimah Sawa’, literally meaning ‘meeting point’. This research will answer three problems, namely; 1). What is the need for contextual exegesis in the discourse of contemporary Islamic thought? 2). How are the dynamics of the development of pluralism in Indonesia? 3). What is the thought of religious pluralism according to Nurcholish Madjid?. By using hermeneutic analysis, the researcher argues that every idea, concept and thought of Islamic thought leaders should not be accepted with the naked eye (taken for granted) without analyzing it in depth, the researcher is compelled to show Nurcholish Madjid’s thoughts on religious pluralism which focus on the Indonesia context. This study concludes that ‘Kalimah Sawa’ has implications for the understanding of religious pluralism, according to Nurcholish is interpreted with the lexical content of ‘Tawhid’ and ‘Islam’. Therefore, the meaning of Islam is a synonim of ‘Kalimah Sawa’ found in Semitic religions with the condition: submission and affirmation of ‘Tawhid’ by the teachings of the previous prophets. Religious pluralism is a religious understanding that elaborates on theological and sociological concepts. Someone who believes in god and has faith must have an impact on social piety